Structural Basis for the Functional Changes by EGFR Exon 20 Insertion Mutations - Tamirat Mahlet Z.; Kurppa Kari J.; Elenius Klaus; Johnson Mark S. (MDPI, 2022)
Simple Summary
Non-small cell lung cancer (NSCLC) is the most common type of lung cancer that claims the lives of many worldwide. Activating mutations occurring on the epidermal growth factor receptor (EGFR) protein have been associated with the pathogenesis of NSCLC, among which exon 20 insertion mutations play a significant role. The objective of this study is to examine the dynamic structural changes occurring on the EGFR protein as a result of two common EGFR exon 20 insertion mutations, V769insASV and D770insNPG. The study further aims to uncover the mechanisms by which the insertion mutations increase kinase activity. Our results suggest that the insertion mutations stabilize structural elements key to maintaining the active EGFR conformation. Furthermore, the insertions disrupt an interaction essential in stabilizing the inactive conformation, which could drive the kinase from an inactive to an active EGFR state.
Abstract
Activating somatic mutations of the epidermal growth factor receptor (EGFR) are frequently implicated in non-small cell lung cancer (NSCLC). While L858R and exon 19 deletion mutations are most prevalent, exon 20 insertions are often observed in NSCLC. Here, we investigated the structural implications of two common EGFR exon 20 insertions in NSCLC, V769insASV and D770insNPG. The active and inactive conformations of wild-type, D770insNPG and V769insASV EGFRs were probed with molecular dynamics simulations to identify local and global alterations that the mutations exert on the EGFR kinase domain, highlighting mechanisms for increased enzymatic activity. In the active conformation, the mutations increase interactions that stabilize the alpha C helix that is essential for EGFR activity. Moreover, the key Lys745-Glu762 salt bridge was more conserved in the insertion mutations. The mutants also preserved the state of the structurally critical aspartate-phenylalanine-glycine (DFG)-motif and regulatory spine (R-spine), which were altered in wild-type EGFR. The insertions altered the structure near the ATP-binding pocket, e.g., the P-loop, which may be a factor for the clinically observed tyrosine kinase inhibitor (TKI) insensitivity by the insertion mutants. The inactive state simulations also showed that the insertions disrupt the Ala767-Arg776 interaction that is key for maintaining the "alpha C-out" inactive conformation, which could consequently fuel the transition from the inactive towards the active EGFR state.